2017
DOI: 10.1111/cas.13245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SMYD2‐mediated EML4‐ALK methylation on the signaling pathway and growth in non‐small‐cell lung cancer cells

Abstract: A specific subtype of non‐small‐cell lung cancer (NSCLC) characterized with an EML4‐ALK fusion gene, which drives constitutive oncogenic activation of anaplastic lymphoma kinase (ALK), shows a good clinical response to ALK inhibitors. We have reported multiple examples implying the biological significance of methylation on non‐histone proteins including oncogenic kinases in human carcinogenesis. Through the process to search substrates for various methyltransferases using an in vitro methyltransferase assay, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…SMYD2 was identified as a lysine methyltransferase (KMT) for histone H3K36 and K370 of p53, and it is reportedly overexpressed in various tumors, including HNSCC 37 , 38 . Recent studies also show that SMYD2 mediates methylation of proteins critical for oncogenesis, including β-catenin and EML4-ALK 39 , 40 . SETD6 was first identified as a KMT for histone H2AZ that controls expression of estrogen-responsive genes and proliferation in breast cancer cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…SMYD2 was identified as a lysine methyltransferase (KMT) for histone H3K36 and K370 of p53, and it is reportedly overexpressed in various tumors, including HNSCC 37 , 38 . Recent studies also show that SMYD2 mediates methylation of proteins critical for oncogenesis, including β-catenin and EML4-ALK 39 , 40 . SETD6 was first identified as a KMT for histone H2AZ that controls expression of estrogen-responsive genes and proliferation in breast cancer cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…SET and MYND domain-containing 2 (SMYD2) is one of the H3K36-specific methyltransferases, which methylates lysine residues in anaplastic lymphoma kinase (ALK) and contributes to oncogenic ALK activation. Combination treatment of a SMYD2 inhibitor LLY-507 and an ALK inhibitor crizotinib exhibited significantly enhanced suppression on NSCLC cell growth compared with mono-treatment of either agent [ 73 ].…”
Section: Kmts and Their Roles In Lung Cancermentioning
confidence: 99%
“…It is also worth noting that epigenetic regulatory genes might be a promising therapeutic target in ALK fusion positive tumors. This is evident in recent studies [ 29 ], which demonstrated that specific lysine residues (e.g., 1451, 1455 and 1610) in EML4-ALK proteins were methylated by a lysine methyltransferase, SET and MYND domain-containing 2 (SMYD2). Preventing methylation of these lysine residues via either knockdown of SMYD2 or treatment with a SMYD2 inhibitor significantly attenuated the phosphorylation levels of EML4-ALK and inhibited downstream AKT activation.…”
Section: Genomic Characteristics Of Alk Fusion-driven Nsclcmentioning
confidence: 85%
“…Preventing methylation of these lysine residues via either knockdown of SMYD2 or treatment with a SMYD2 inhibitor significantly attenuated the phosphorylation levels of EML4-ALK and inhibited downstream AKT activation. More strikingly, combination treatment with a SMYD2 inhibitor and an ALK inhibitor additively suppressed the growth of NSCLC cells, compared with single-agent treatment [ 29 ]. Therefore, the complexity of ALK fusion protein-mediated signaling, activated not only by constitutive phosphorylation within the kinase domain, but also by methylation of the ALK protein, together with epistatic effects of co-occurring mutations, could be of central importance for the development of potent next generation ALK inhibitors and the design of combinational therapeutic approaches.…”
Section: Genomic Characteristics Of Alk Fusion-driven Nsclcmentioning
confidence: 99%